Ambient levels of concentrated PM2.5 affects cell kinetics in adrenal glands: an experimental study in mice. (3rd June 2017) - Fuchs, Luiz Fernando Portugal; Veras, Mariana Matera; Saldiva, Paulo Hilário Nascimento; Sasso, Gisela Rodrigues da Silva; Carvalho, Kátia Cândido; Simões, Manuel de Jesus; Soares, José Maria; Baracat, Edmund Chada
Abstract: We evaluated the effects of air pollution on the adrenal cortex using 30 female mice divided into two groups of fifteen animals each. One group was conditioned daily in a chamber with exposure to particulate matter (PM) 2.5 μm (GExp). Animals were exposed on daily basis in an ambient particles concentrator during the period of time enough to reach an accumulated dose of 600 μg/m 3, which corresponds to a 24-h exposure of 25 μg/m 3 that approximates to the annual mean of PM2.5 in São Paulo. The other group was allocated to another chamber with filtered air (GCrt). After euthanasia, the adrenals underwent histological processing and immunohistochemistry staining for Ki-67 and cleaved caspase-3. Histomorphometry of the adrenal glands in GExp showed increased thickness of the zona glomerulosa, while in GCrt; the adrenal glands from GExp had higher Ki-67 immunostaining scores in the zona reticularis than those from GCrt. The adrenal from GExp showed higher cleaved caspase-3 immunoreactivity in the zona fasciculata than the unexposed group (GCrt). The homeostasis index indicated higher cell proliferation in the zona glomerulosa and zona reticularis in GExp than in GCrt. Our data indicate that PM2.5 air pollution induces alterations on cell kinetics in mouse adrenal glands.